Studies on complexes of Co(II), Ni(II), Cu(II), and Cd(II) with acetophenone and 4-hydroxyacetophenone benzoylhydrazones - Singh B.; Narang K.K.; Srivastava R. (My University, 2025)
Metal(II) complexes of the types [M(L)2Cl2] · H2O and [Cu(4-HOABH)SO4(H2O)2] [M = Co(II), Ni(II), Cu(II) and Cd(II), L = acetophenone benzoylhydrazone (ABH), C6H5CONH-N=C(CH3)C6H5 and 4-hydroxyacetophenone benzoylhydrazone (4-HOABH), C6H5CONHN=C(CH3)C6H4OH], were prepared and characterized by elemental and thermal analyses, molar conductance, infrared, ESR and electronic spectral studies. Some of the complexes were screened against E. coli and Aspergillus niger for biological activity.